Diversity in the workforce - DiTomaso, Nancy; Post, Corinne (Research in the sociology of work ;, 2004)
Increasing diversity in the workforce has several sources: (a) the changing demographic structure of the U.S., (b) the increased importance of globalization to profits and long term survival in many companies, and (c) changes in the structure of how work gets done. People bring with them into organizations the patterns of behavior and thinking, the networks, the social pressures, the habits, and strategies of action that they learned before joining the organization. Further, people are shaped by the perceptions, attitudes, and behaviors of others in regard to them. Although many organizations in the past have tried to homogenize behavior and attitudes by developing their own organizational cultures, the reality in most organizations is the existence of distinct subcultures and microcultures, as each group tries to find its own place, often in competition with others. This volume of the Sociology of Work addresses a number of issues that are brought to the fore because of diversity in the workforce: the structure, impact, and mechanisms of social networks; the policies and political dynamics around trying to redistribute benefits among social groups; issues regarding work and family, especially for professional workers in male dominated jobs; and the link between diversity in the workforce and broader issues of inequality. This set of papers address many of the emerging empirical and theoretical work in the study of diversity in the workforce and create an agenda for future work in the area.